The drugs, interacting with opiate receptors, and their application in gastroenterological practice - S. A. Bulgakov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present information on the drugs nowadays used in gastroenterology, that interact with opiate receptors. Original positions. Opiate receptors in the body have been discovered about 35 years ago. For this time their various types have been found, many peptides are discovered, their classes are characterized. Methods of peptide chemistry provide synthesizing hundreds of endogenous peptide compound analogues. On their basis new medicamental agents were developed. The first-ever synthetic drug manufactured on the basis of leucine-enkephaline, was the Russian drug dalargin. Article presents features of its synthesis, pharmacological effects, main directions of application: peptic ulcer of the stomach and duodenum, pancreatitis. Compounds of non-peptide nature, capable to interreact with opiate receptors are used now as well. There is information on loperamide, diphenoxylate, trimebutine and fedotozine – all these drugs find their application in treatment of intestinal diseases. Conclusion. The drugs interacting with opiate receptors, are widely used in gastroenterological practice and there are preconditions to broaden spectrum of these agents.